Dry sliding wear behaviour of Ti–6Al–4V pin against SS316L disc in vacuum condition at high temperature. (3rd July 2019) - Kumar, Deepak; Lal, Basant; Wani, M. F.; Philip, Jibin T.; Kuriachen, Basil
ABSTRACT: Ti–6Al–4V alloy exhibit a unique combination of mechanical, physical, and chemical properties; that pronounced its desirability for implementation in the fields of aerospace, automobile, and chemical industries. The mechanisms, namely, strain rate response/adiabatic shear band (ASB) – effect of plastic deformation, tribo-chemical reaction and formation of the mechanically mixed layer (MML), can control wear behaviour of the alloy. Hence, the present work investigates the influence of these mechanisms in governing the tribological characteristics of the Ti6Al4V alloy aganist SS316L steel. The experiments were executed on a pin-on-disc tribometer under vacuum (2 × 10 −5  Torr), by varying the temperature (25, 100, 200, 300 and 400°C) at constant sliding speed (0.01 ms −1 ) and load (137.3 N) conditions. Compression test was carried out at distinct strain rate (0.001 and 10 s −1 ) and temperature (25, 100 and 400°C) values, to investigate the occurrence of ASB. The scanning electron microscopy and energy dispersive X-ray spectroscopy analyses were used to evaluate the formation of appendage layers (oxides and MML) and the composition of wear debris, respectively. The wear rate of the Ti–6Al–4V alloy decreased with increment in temperature (room condition to 400°C) inside vacuum environ, governed by ASB and the presence of oxide layers.